Overparenting and psychological well-being among Asian American young adults: the role of gender & parent-child conflict - Koh, Cheryl Jie Xin (Nanyang Technological University, 2023)
Research suggests that the excessive involvement by parents in the form of overparenting can be detrimental to children’s well-being. This cross-sectional study examined whether this negative association between overparenting and psychological well-being generalizes to Asian American young adults and how cultural factors, such as parent-child conflict and gender, contribute to this overparenting-well-being relation. Participants were 297 college students (18−25 years old) from two public universities in the United States. College students completed questionnaires on overparenting, parent-child conflict and their levels of anxiety and depression. We conducted a moderated mediation analyses to test whether (1) parent-child conflict mediated the relation between overparenting and anxiety and depression; and (2) gender moderated this indirect explanatory model. The study found that overparenting was positively associated with anxiety and depression. Overparenting was also indirectly associated with anxiety and depression via parent-child conflict. Gender differences were also found where females who experienced overparenting were more likely to experience higher levels of parent-child conflict and this was associated with higher levels of depression. The findings suggest that Asian Americans are at risk for poorer psychological well-being when they experience overparenting and that females who experience overparenting may experience higher risk of depression than males, highlighting the need for targeted interventions.